CHANGING ROLE OF HR MANAGERS AND ITS IMPACT ON ORGANISATIONAL SUCCESS - Kaushik, Anshu; Ruhela, Sakshi; Tomar, Prashant; Trivedi, Ritesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper discusses about the changing roles of HR manager in modern times and how these roles have an impact on organizational success. As the business environment is so dynamic and technology is upgrading day by day there is a shift in HR roles from staffing function to HR Development and HR Business Partners to meet the organizational needs and the performance. The main objective of the study is to understand the recent trends in HRM and how these trends affect the role of HR Manager. The study reveals that various methods, strategies etc. act as a catalyst for HR managers to play their changing roles effectively and efficiently. The paper also describes the challenges faced by HR manager to fulfill the emerging roles of HR manager.